MEMAKNAI KEMARAHAN ALLAH DARI SUDUT PANDANG TEOLOGI PENTAKOSTA DI ERA POST MODERN - Kosma Manurung (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
This article intends to give meaning to God's anger in the light of Pentecostal theology. The methodology used is text analysis and literature review. There are four examples of God's anger that were studied, namely God's anger towards Adam and Eve, God's anger towards the Israelites, the anger of the Lord Jesus towards the disciples, and the anger of the Lord Jesus towards the merchants in the Temple. The research results show that Allah is never angry for no apparent reason, and every anger of Allah is impacted. The causes of God's anger are disobedience, replacing God with other gods, injustice, and trading services. The impact of God's anger is separation from God, loss of the religious community, bringing God's judgment, and death.